(untitled) (Docentes 2.0 Journal, 2016)
Teaching programs are only based on linguistic and mathematical intelligences, giving minimal importance to the others. That is why, in order to achieve the objective of transforming the traditional educational institution into one of Multiple Intelligences, it is necessary to start from a team work involving the school (teachers), and the home (the parents).